Developing English language material integrated with Duolingo App for young learners in UNU Yogyakarta English Club Program - Maratussholihah Maratussholihah; Khusnul Harsul Lisan; Harisna Hikmah (MASI Mandiri Edukasi, 2026)
English learning materials for young learners in Indonesia are often limited in interactivity and the integration of digital learning resources that are appropriate to the characteristics of student learning, especially in the context of extracurricular learning. This study aims to develop English learning materials by integrating the Duolingo App and to evaluate the suitability of the materials developed for use in the UNU Yogyakarta English Club program. This study applied the Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The need analysis data were taken from pre-test results involving 57 students enrolled in the English program, semi-structured interviews with parents, and expert judgment for material validation. The developed English learning materials were designed and developed into ten learning units integrating the Duolingo App, equipped with printable worksheets and interactive learning activities. Expert validation was conducted by one expert in learning materials and learning models across five aspects: content, design, motivation, and the feasibility of the developed materials. The expert validation yielded a score of 4.18, indicating that this learning material is good and suitable as a supporting medium for English language learning. The implementation stage involves applying the developed materials in actual classes, followed by evaluation through observation and analysis of student performance at the end of each learning session. The study’s findings show that the pedagogically developed material is appropriate for classroom use. Students showed positive responses in terms of engagement, motivation, and participation during the learning process.